Religion, Politics, And Globalization : Anthropological Approaches. - Alina (Berghahn Books, 2013)
While social scientists, beginning with Weber, envisioned a secularized world, religion today is forthrightly becoming a defining feature of life all around the globe. The complex connections between religion and politics, and the ways in which globalization shapes these processes, are central themes explored in this volume by leading scholars in the field of religion. Does the holism of numerous past and present day cosmologies mean that religions with their holistic orientations are integral to human existence? What happens when political ideologies and projects are framed as transcendent.